Coins and power in late Iron Age Britain - Creighton, John, 1964- (New studies in archaeology., 2000)
Combining archaeological, literary and numismatic evidence, John Creighton paints a vivid picture of how people in Late Iron Age Britain reacted to the changing world around them, and how rulers bolstered their power through use of imagery on coins, myths, language, and material culture. Includes full index of Iron Age coins.